Witchcraft Narratives among the Tallensi of Ghana - Adu-Gyamfi, Samuel; Tibil Bersong, Dennis; Yakubu Nyaaba, Ali (Universitas Islam Indonesia, 2024)
Witchcraft and related issues have been part of African metaphysics. It remains one of the most important human predicaments and dynamics that most scholars find difficult to comprehend. Witchcraft accusations have reached alarming rates in the Tallensi District and the five regions of northern Ghana as a whole. Among the Tallensi, accused witches or wizards were sometimes murdered by their people on the advice of a diviner from another community. Sometimes, too, when the diviner confirmed an individual or group of people as witches, they were permanently cast out or expelled from the Tallensi community. There are several academic scholarly works on witchcraft worldwide. They have been closely examined, based on anti-witchcraft shrines, children's witchcraft, ‘witch camps’ accusations, alleged witches, and ethnically related witches and affiliates. However, the current research investigates the concept of witchcraft in a global society and how people understand and relate to it in their respective communities, particularly Tallensi. It also focuses on how one could be identified as a witch or wizard in his/her community, as well as the treatment that was meted out to him/her. Finally, this study sheds more light on the role of traditional indigenous shrines in the discussion of witchcraft among the Tallensi. To achieve this, the research relied on historical sources to re-evaluate the monograph of Meyer Fortes, who argued that witchcraft and its related activities are strange to Tallensi. The current contribution also discusses the increasing role of Christian interpretation of scripture concerning witchcraft and how the same has aggravated the witchcraft quandary in Tallensi. A qualitative research approach based on both primary and secondary data sources was employed in this study. The analysis revealed that, even though people believed in the existence of witchcraft, none could provide empirical evidence to prosecute a witch or wizard. Overall, the study also established that accused witches live a life of misery in their respective communities, even if they are not murdered or banished. Ironically successive governments in Ghana have done little to ameliorate the plight of these people, but they always solicit their vote during periods of elections in the country.